2017
DOI: 10.1002/jms.3958
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound analysis by pulsed glow discharge time of flight mass spectrometry as a structural elucidation tool

Abstract: Pulsed glow discharge (PGD) coupled to time of flight mass spectrometry (TOFMS) has been investigated for volatile organic compound (VOC) identification and determination. Optimization of PGD operational conditions (chamber design, applied power, pressure and duty cycle) was performed using acetone and benzene as model compounds. During the different optimizations, molecular, fragment and elemental information were obtained when characteristic GD pulse regions were measured. An exploratory study for several VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The LOD values in the range of 0.5-5 ppb were achieved, which is perspective for the real application of the new approach for a wide range of analytical tasks, including the determination of VOCs in human exhalation. 15,16 When comparing our results with previous studies, 1,3,5 the following aspects may be identified. The combination of several factors related to the nature of the pulsed glow discharge resulted in the combination of two beneficial outcomes for the online detection mode, which are often hard to achieve together.…”
Section: No + + M → No + M +supporting
confidence: 55%
See 3 more Smart Citations
“…The LOD values in the range of 0.5-5 ppb were achieved, which is perspective for the real application of the new approach for a wide range of analytical tasks, including the determination of VOCs in human exhalation. 15,16 When comparing our results with previous studies, 1,3,5 the following aspects may be identified. The combination of several factors related to the nature of the pulsed glow discharge resulted in the combination of two beneficial outcomes for the online detection mode, which are often hard to achieve together.…”
Section: No + + M → No + M +supporting
confidence: 55%
“…Bouza et al also used the Penning mechanism for VOC ionisation. 1 However, since Ar* rather than N2* was used for the ionisation, which has a higher excitation energy (the difference of 0.66 eV), it resulted in a significantly higher fragmentation level for the VOCs. 1 Besides, we used a relatively low discharge power of 3 W, additionally reducing the degree of fragmentation.…”
Section: No + + M → No + M +mentioning
confidence: 99%
See 2 more Smart Citations
“…Complex ionization methods such as atmospheric pressure chemical ionization (APCI), dielectric-barrier discharge ionization (DBDI), and glow discharge , are also common ionization technologies that have been developed for the direct sensitive detection of volatile organic or inorganic compounds. In the process of complex ionization, all or parts of EI, SPI, CI, and Penning ionization may co-occur in the ionization region.…”
mentioning
confidence: 99%